Elliptic Operators in a Refined Scale of Functional Spaces - Mikhailets, V. A.; Murach, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We study the theory of elliptic boundary-value problems in the refined two-sided scale of the Hormander spaces $H^{s, φ}$, where $s \in R,\quad φ$ is a functional parameter slowly varying on $+∞$. In the case of the Sobolev spaces $H^{s}$, the function $φ(|ξ|) \equiv 1$. We establish that the considered operators possess the properties of the Fredholm operators, and the solutions are globally and locally regular.